Strategies to Introduce Social-Emotional Skills in Early Children Through Animal Stories Books We Are Friends, Let's Collect Friendship Fables by Chandra Wening - Somadayo, Samsu; Larasati, Falasifa; Kurniawan, Heru (International Proceedings of Nusantara Raya, 2022)
There are many ways to introduce social-emotional skills to early childhood, one of which is storytelling. Researchers took three strategies to introduce social-emotional skills in early childhood through animal storybooks that parents and educators could read, these three strategies include a strategy for reading picture stories, a storytelling strategy using hand puppet media, and a strategy using flannel board media. The data collection technique used by researchers is the documentation method. This research is an analysis of an animal storybook for early childhood.